2021
DOI: 10.9734/jpri/2021/v33i43b32532
|View full text |Cite
|
Sign up to set email alerts
|

Review on Transferosomes and Transferosomal Gels

Abstract: Transdermal drug delivery systems (TDDS), which are self-administrable and non-invasive, can improve bioavailability and patient compliance by bypassing first-pass metabolism. Vesicular-based TDDS have attracted a lot of attention in recent years because they're designed for controlled, efficient, and targeted drug delivery. One of these delivery technologies, transferosomal-based formulations, has grown in popularity due to its ability to achieve all of the desired criteria and quality qualities. Transferosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Transferosomes can spontaneously penetrate the stratum corneum (SC) because they can efficiently cross a variety of transport barriers [81]. They have better efficacy in sustained release applications for topical medication administration and are more elastic than liposomes [82,83]. A study showed that transferosomes encapsulated RSV has more penetration power (27.5%) in comparison with free RSV [84].…”
Section: Transferosomesmentioning
confidence: 99%
“…Transferosomes can spontaneously penetrate the stratum corneum (SC) because they can efficiently cross a variety of transport barriers [81]. They have better efficacy in sustained release applications for topical medication administration and are more elastic than liposomes [82,83]. A study showed that transferosomes encapsulated RSV has more penetration power (27.5%) in comparison with free RSV [84].…”
Section: Transferosomesmentioning
confidence: 99%
“…They serve as depots and release their contents gradually. 30 , 31 They can be utilized for both systemic and topical medication delivery. Because the technique is uncomplicated and avoids needless use of pharmaceutically undesirable ingredients, they are simple to scale up.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental drawback of transferosomes is that they are prone to oxidative destruction, which makes them chemically unstable. 30 …”
Section: Introductionmentioning
confidence: 99%